Estudos dos mecanismos envolvidos na ação antinociceptiva causada pelo disseleneto de difenila em camundongos - Savegnago, Lucielli (2007)
The interest in organoselenium biochemistry and pharmacology has increased in the last two decades due to a variety of organoselenium compounds that possess biological activity. Accordingly, diphenyl diselenide, a simple diaryl diselenide, is known as a safety drug when administered acutely to mice at doses that have antiinflammatory and antinociceptive activities. Therefore, the research of the mechanisms by which this compound exerts its effects is extremely important for the therapeutic application. Based on the considerations above, the aims of the present study were to evaluate the acute toxicity induced by diphenyl diselenide in mice using oral route of administration with the purpose of offering safety in the use of this compound and to verify the antinociceptive and antiinflammatory activities caused by diphenyl diselenide as well as its mechanisms of action. Diphenyl diselenide administered orally produced minor toxicological effects which were evidenced by the index of mortality (lethal-dose > 312 mg/kg). Although diphenyl diselenide did not provide evidence for renal or hepatic toxicity, the body weight gain in mice exposed to this compound was reduced, which might indicate systemic toxicity. The oral administration (p.o.) of diphenyl diselenide inhibited acetic acid-induced abdominal constriction as well as capsaicin-, glutamate- bradykinin (BK)- phorbol myristate acetate (PMA)- and formalin induced nociception and caused a significant increase in tail-immersion response latency time. In addition, diphenyl diselenide co-injected intraplantarly (i.pl.) in association with glutamate induced a significant reduction of the licking and in the paw oedema formation induced by glutamate. The local pretreatment of mice with L-arginine and dithiothreitol (DTT; i.pl.) restored local antinociception caused by diphenyl diselenide when analyzed against glutamateinduced nociception. Moreover, diphenyl diselenide, given orally, caused significant inhibition of the biting behavior induced by intrathecal (i.t.) injection of glutamate, Nmethyl-D-aspartate (NMDA), substance P (SP), interleukin 1b (IL-1b), tumor necrosis factor-a (TNF-a), BK and capsaicin, but completely failed to affect the nociception induced by α-amino-3-hydroxy-5-mehtyl-4-isoxazolepropionic acid (AMPA), kainate and (±)-1-aminocyclopentane-trans-1,3-dicarboxylic acid (trans-ACPD). The antinociceptive effect caused by diphenyl diselenide in the formalin test was reversed by i.t. injection of several K+ channel blockers such as apamin and charybdotoxin (large- and small-conductance Ca2+- activated K+ channel inhibitors, respectively), tetraethylammonium (TEA, non-selective voltage-dependent K+ channel inhibitor), but not glibenclamide (ATP-sensitive K+ channel inhibitor). Injection of mice with inhibitor of nitric oxide (NO) synthase (Nω-nitro-L-arginine; L-NOARG), guanylyl cyclase inhibitors (1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one - ODQ; and methylene blue) and calcium chloride (CaCl2) significantly blocked the antinociceptive effect caused by diphenyl diselenide when assessed on the formalin test. In contrast, i.t. injection of pertussis toxin, an inactivator of Gi/0 protein, did not antagonize the antinociceptive action caused by diphenyl diselenide in the formalin test. Diphenyl diselenide increased nociceptive threshold in mechanical allodynia induced by both partial sciatic nerve ligation (neuropathic pain) and ACF i.pl. injection (inflammatory chronic pain) as well as attenuated acute thermal hyperalgesia induced by i.t. injection of glutamate, NMDA, BK and prostaglandin E2 (PGE2). Together these results suggested the participation of nitric oxide/cyclic GMP/Ca2+ and K+ channel, pathways, inhibition PKA e PKC, as well as glutamatergic, peptidergic and vanilloid systems in the antinociceptive action caused by diphenyl diselenide in mice.